Personalist ruling parties in democracies. Issue 5 (4th July 2022) - Frantz, Erica; Kendall-Taylor, Andrea; Li, Jia; Wright, Joseph
ABSTRACT: This study introduces a new data set on personalism in ruling parties across the world's democracies. We conceptualize party personalism as the extent to which parties are vehicles to advance leaders' personal political careers such that the leader has more control over the party than do other senior party elites and compare this concept with related ones. After describing the measurement strategy and demonstrating measurement reliability and validity, we show the global and historical patterns of ruling party personalism in the past three decades. We then use this measure to examine whether personalist ruling parties shape two outcomes relevant to the quality of democracy: political polarization and citizen satisfaction with democracy. We show that when leaders backed by a personalist political party win power, political polarization increases; we do not find that party personalism influences citizen support for democracy, however. Our findings suggest that the election of leaders supported by personalist political parties sets in motion meaningful political changes, though not in all the domains observers have proposed. We close this study by discussing additional areas in which our data can be used in future research.